Disseminated histoplasmosis and AIDS: a prospective and multicentre study to evaluate the performance of different diagnostic tests. Issue 1 (22nd July 2016) - Hoffmann, E. R.; Daboit, T. C.; Paskulin, D. D.; Monteiro, A. A.; Falci, D. R.; Linhares, T.; Flores, J. M.; Goldani, L. Z.; de Melo, M. G.; Behar, P. R.; Pasqualotto, A. C.
Summary: The burden of histoplasmosis has been poorly documented in most of the endemic areas for the disease, including Brazil. Also, modern non‐culture‐based diagnostic tests are often non‐available in these regions. This was a prospective cohort study in HIV‐infected patients with suspected disseminated disease evaluated with different diagnostic tests. Patients were enrolled in three referral medical centres in Porto Alegre, Brazil. Among 78 evaluated patients, disseminated histoplasmosis was confirmed in eight individuals (10.3%) by the means of classical (culture/histopathology) tests. Antigen detection in the urine was found to be more sensitive: IMMY ® ALPHA ELISA detected 13 positive cases (16.7%) and the in‐house ELISA test developed by the Centers for Disease Prevention and Control (CDC) detected 14 (17.9%). IMMY ® and CDC tests provided concordant results in 96.2% of cases. This is the first study to compare the performance of the in‐house CDC ELISA test with the IMMY ® commercial test for the diagnosis of histoplasmosis, and a high degree of concordance was observed. The study revealed that H. capsulatum is an important agent of disseminated disease in AIDS patients in Brazil, reinforcing the importance of making available modern diagnostic tests as well as safer antifungal agents for the treatment of histoplasmosis.